Conceptual Framework of Risk Control as Moderator on the Relationship between Determinant Factors Selection and Performance of SMEs in Indonesia: A Pilot Study - Guci, Dede Ansyari; Puspa Liza Ghazali; Nik Hazimi Mohamad Foziah; Zainuddin Awang (International Journal of Entrepreneurship and Business Management, 2022)
Only SMEs are successful: Indicates a gap in some effective ways to increase the size of faction while the achieving extraordinary performance and sustainable growth. Purpose – This paper aimed to help fill the gap by identifying factors related to SMEs performances and develop the conceptual framework to explain the relationships. This paper aimed to help fill the gap by identifying factors related to SMEs performances and develop the conceptual framework to explain the relationships. Some literatures showed a positive relationships among the variables; but the relationship is not yet decisive. The field observation and literary assessments suggest a secondary configuration that play a complete role among government supports, training, digital marketing, financial capital and small business performances, and also the risk control. Although the relationships among the six structures of the whole literatures were examined in detail, this article is one of several efforts in the study of six constructs in a comprehensive framework for further research. With empirical support, the proposed framework can provide effective alternatives to help entrepreneurs and small business players to develop their businesses effectively. Methodology/approach – The data was collected by using questionnaires and analyzed the KMO and Barlett’s Test by using SPSS 21 from about 100 respondents as entrepreneurs in small businesses in Medan, Indonesia. Findings – The result showed that all measured variables were >0.50, means that the strong relationships among items need to be investigated. Novelty/value – As SMEs have the important role in economics for developing country like Indonesia, it is vital to understand how to increase the performance of SMEs.